Development of the methodological approach of obtaining preparations based on solid dispersions - Kovalevska, Inna; Ruban, Olena (ScienceRise: Pharmaceutical Science, 2018)
Nowadays, the innovative direction of pharmaceutical development is the application of methods to increase the biopharmaceutical efficiency and safety of the use of already existing APIs, including method of incorporating them into solid dispersions in which the substance molecules are included in the supramolecular formations by forming non-covalent bonds by excipients. Today, the preparation of solid dispersions is considered as the most effective way of increasing oral bioavailability, in which dissolution of the carrier facilitates the release of API with its rapid solubilization. According to the literature, it is established that today there is only an empirical approach to obtaining solid dispersions. The aim of the work was the formulation of the main approaches to the development of preparations on the basis of solid dispersions, taking into account the current trends in the development of the composition and technology of preparations with sparingly soluble active pharmaceutical ingredients. Materials and methods. To develop a methodological approach, external situational content analysis of applied methods for increasing the bioavailability of active pharmaceutical ingredients used in the manufacture of solid dosage forms was used. Results. In the course of accomplishing this goal, a classification of the types of solid dispersions was proposed depending on the structure and method of production, an algorithm was developed for choosing a method for obtaining a solid dispersion, taking into account the physico-chemical properties of the active pharmaceutical ingredients, which can be used in the technological process to increase their bioavailability. Critical components were also found in the development of solid dispersions. Conclusions. Taking into account the physicochemical properties of the active pharmaceutical ingredients, was chosen an algorithm for selecting a method for preparing solid dispersions that can be used in the process to improve their bioavailability. Based on the results of the analysis of the literature data and our own research of the physico-chemical characteristics of the active pharmaceutical ingredients and excipients, type of the solid dispersion structure, the type of solvent and carrier, a methodological approach to the preparation of solid dispersions is proposed, the use of which will optimize the development of solid dosage forms